Influence of pro-angiogenic cytokines on proliferative activity and survival of endothelial cells - Garmanchouk, L.V.; Pyaskovskaya, O.N.; Solyanik, G.I. (Вiopolymers and Cell, 2010)
Tumor angiogenesis in contrast to physiological one is characterized by high level of malignant cell production of proangiogenic cytokines, which have different influence on functional activity of endothelial cells. The aim of the study – to carry out a comparative analysis of the influence of a vascular endothelial growth factor (VEGF) and an epidermal growth factor (EGF) on proliferative activity and survival of endothelial cells upon their confluent and exponential growth. Methods. The proliferative activity of endothelial cells was determined by MTT-test and their viability was detected by the trypane blue exclusion test. Results. It was shown that EGF (irrespectively of the level of serum factors) in concentrations higher than 10 ng/ml activated the proliferative activity of confluent endotheliocytes in a concentration-dependent manner by 18–36 % (p < 0.05) as compared to the control, while this cytokine did not affect the endothelial cells in the exponential growth phase. VEGF in wide concentration range did not display the mitogenic effect on endotheliocytes in both confluent and exponential growth phases. Furthermore, VEGF in concentrations higher than 100 ng/ml inhibited proliferative activity of confluent endothelial cells by 12 % (p < 0.05). In case of deficiency of nutrients, EGF and VEGF promoted the survival of endothelial cells, considerably decreasing their death. Conclusions. EGF, in contrast to VEGF, stimulates proliferation and survival of the endothelial cells, whereas VEGF has significant influence only on the survival of the cells. Пухлинний ангіогенез на відміну від фізіологічного характеризується високим рівнем продукування пухлинними клітинами проангіогенних цитокінів, які по-різному діють на функціональну активність ендотеліальних клітин. Мета роботи – провести порівняльний аналіз впливу фактора росту ендотеліальних клітин (VEGF) та епідермального фактора росту (EGF) на проліферативну активність і виживання ендотеліальних клітин за їхнього експоненційного та конфлюентного росту. Методи. Проліферативну активність і виживання ендотеліальних клітин лінії МАЕС під впливом EGF та VEGF визначали за МТТ-тестом і підрахунком живих клітин з використанням трипанового синього. Результати. EGF (незалежно від рівня сироваткових факторів) у концентраціях, більших за 10 нг/мл, активує проліферативну активність ендотеліоцитів за умов конфлюентного росту на 18–36 % (р < 0,05) ефективніше порівняно з контролем, тоді як при експоненційному рості ендотеліоцитів суттєвого впливу зазначеного цитокіну на проліферацію клітин не виявлено. VEGF у широкому діапазоні концентрацій не проявляє мітогенного ефекту на ендотеліоцити за умов як конфлюентного, так і експоненційного росту. Більше того, у концентраціях, вищих за 100 нг/мл, VEGF на 12 % (р < 0,05) інгібує проліферативну активність ендотеліальних клітин в умовах конфлюентного росту. У разі дефіциту сироваткових факторів обидва цитокіни сприяють виживанню ендотеліальних клітин, суттєво зменшуючи їхню загибель. Висновки. EGF на відміну від VEGF стимулює як проліферацію ендотеліальних клітин, так і їхнє виживання, тоді як VEGF сприяє лише виживанню ендотеліоцитів. Опухолевый ангиогенез в отличие от физиологического характеризуется высоким уровнем продуцирования опухолевыми клетками проангиогенных цитокинов, по-разному влияющих на функциональную активность эндотелиальных клеток. Цель работы – провести сравнительный анализ действия фактора роста эндотелиальных клеток (VEGF) и эпидермального фактора роста (EGF) на пролиферативную активность и выживаемость эндотелиальных клеток при их конфлюэнтном и экспоненциальном росте. Методы. Пролиферативную активность и выживаемость эндотелиальных клеток линии МАЕС при влиянии EGF и VEGF определяли МТТ-тестом и подсчетом живых клеток с использованием трипанового синего. Результаты. EGF (независимо от уровня сывороточных факторов) в концентрациях выше 10 нг/мл активирует пролиферативную активность на конфлюэнтной стадии роста эндотелиоцитов на 18–36 % (р < 0,05) эффективнее по сравнению с контролем, тогда как при экспоненциальном росте эндотелиоцитов существенного влияния этого цитокина на пролиферацию клеток зафиксировано не было. VEGF в широком диапазоне концентраций не проявляет митогенного эффекта на эндотелиоциты при их конфлюэнтном и экспоненциальном росте. Более того, в концентрациях выше 100 нг/мл VEGF на 12 % (р < 0,05) ингибирует пролиферативную активность эндотелиальных клеток при конфлюэнтном росте. В случае дефицита сывороточных факторов оба цитокина способствуют выживанию эндотелиальных клеток, существенно уменьшая их гибель. Выводы. EGF в отличие от VEGF стимулирует как пролиферацию эндотелиальных клеток, так и их выживаемость, тогда как VEGF способствует только выживаемости эндотелиоцитов.